Analisis Kesiapan Kerja Mahasiswa Tingkat Akhir - Maya Zunita; Yusmansyah Yusmansyah; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2018)
The purpose of this research was to find out the final-year students’ employability. This is quantitative descriptive research. The descriptive percentage and Rasch Model were used as the techniques. The sample of this research was the final-year students’ of departement language and arts education program, especially the Indonesian and Literature, English, and French Education students. The total number of the sample was 77 students. The instruments of this research were the employability scale. The result showed that the level of the final-year students’ employability of Indonesian and Literature  (84%), English (94%) and French Education study program (93%) was generally high. This indicated that the employability at the final-year students’of Indonesian and Literature, English, and French Education study program was generally into high category.Tujuan penelitian ini untuk mengetahui tingkat kesiapan kerja mahasiswa tingkat akhir. Penelitian ini bersifat kuantitatif deskriptif, dengan teknik analisis data deskriptif prosentase dan Rasch model. Sampel penelitian sebanyak 77 mahasiswa yang diambil dari program studi Pendidikan Bahasa dan Sastra Indonesia, Bahasa Inggris, dan Bahasa Prancis. Teknik pengumpulan data menggunakan skala kesiapan kerja. Hasil penelitian menunjukan bahwa tingkat kesiapan kerja mahasiswa tingkat akhir program studi Pendidikan Bahasa dan Sastra Indonesia (84%), Bahasa Inggris (94%), dan Bahasa Prancis (93%) yang dapat dikategorikan tinggi. Dapat disimpulkan bahwa kesiapan kerja mahasiswa tingkat akhir program studi Pendidikan Bahasa dan Sastra Indonesia, Bahasa Inggris, dan Bahasa Prancis termasuk dalam kategori tinggi.Kata kunci: bimbingan konseling, kesiapan kerja, mahasiswa